Metode Mengatasi Browning pada Eksplan Ulin (Eusideroxylon zwageri) untuk Inisiasi Regenerasi Secara In Vitro - trios carito; Sulistiawati sulistiawati; Ratna Nirmala (Jurnal Agroekoteknologi Tropika Lembab, 2019)
Ulin (Eusideroxylon zwageri) is one of the native plants of Indonesia whose growth is spread in tropical forest, among others in southern Sumatra and Kalimantan. Based on the results of the 1998 Asia Regional Workshop meeting held at the Hanoi (Vietnam) International Union for Conservation of Nature and Natural Resources (IUCN), it was determined that ironwood is on Vulnerable A1cd + 2cd status which means sensitive or is facing a high risk of extinction. Tissue culture is a technique that needs to be applied to overcome the problem of ironwood regeneration initiation. However, the concentration of tannin with high concentration so that the formation of browning which leads to the death of ulin tissue is one of the causes of the low success of ironwood tissue culture. This study was formulated based on the potential of activated charcoal and vitamin C to overcome browning, so that it can significantly affect the growth of Ulin regeneration initiation (Eusideroxylon zwager). The analytical method used is Observation of Qualitative Parameter Treatment, namely explant color and the quantitative parameter observed is the number of explants that have browned and not browned in this case are calculated in percent. Based on the results of the research that has been done, obtained methods to overcome browning in ulin explants (Eusideroxylon zwageri) which is divided into 2 stages. In stage 1 (pre-condition) browning can be overcome with a 100% success rate, explants soaked for 24 hours in 50% MS liquid media with pH 4. In stage 2, browning can be overcome with a 100% success rate on 100% MS solid media addition of BAP 1.0 mg / L with A2B3 treatment (Vitamin C / 1 mg / L ascorbic acid, 4.00 g / L activated charcoal) placed in the dark room.